Guided Inquiry-Based Questions Integrated Practice Worksheets Design to Improve Laboratory Skills and Knowledge - Khasanah, Faizatul; Susilaningsih, Endang; Nuswowati, Murbangun (Journal of Innovative Science Education, 2017)
The essence of learning Science is not just remembering and understanding the concept but also a habitual behavior in finding concepts. Science learning requires a laboratory to train students' skills. Complete laboratory will be useful if used as possible. The Worksheet Practice design with guided inquiry approach is needed to facilitate students in conducting laboratory experiments. This study aims to determine the feasibility of integrated Worksheet Practice design based on guided inquiry and effectiveness of student laboratory skills. The research design used is one group pretest and post test design. Research data obtained by observation method, documentation, questionnaire, and test. The results obtained mean score 80.56 on the presentation aspect, 81.25 on the content feasibility aspect, 81.95 on aspects of graphical aspect, and 82.50 on the language aspect with maxsimal score 100. The results showed that Worksheet Practice design with guided inquiry approach is categorized as very feasible and can improve students' laboratory skill and knowledge. Hakikat belajar Sains tidak sekedar mengingat dan memahami konsep melainkan juga merupakan pembiasaan perilaku dalam menemukan konsep. Pembelajaran sains memerlukan laboratorium untuk melatih keterampilan siswa. Laboratorium lengkap akan bermanfaat apabila digunakan sebaik mungkin. Desain Lembar Kerja Praktikum dengan pendekatan inkuiri terbimbing diperlukan untuk mempermudah siswa dalam melakukan percobaan di laboratorium. Penelitian ini bertujuan untuk mengetahui kelayakan desain Lembar Kerja Praktikum terpadu berbasis inkuiri terbimbing serta keefektifannya terhadap keterampilan laboratorium siswa. Desain penelitian yang digunakan adalah one group pretest and post test design. Data penelitian diperoleh dengan metode observasi, dokumentasi, angket, dan tes. Hasil penelitian diperoleh rerata skor 80,56 pada aspek penyajiaan 81,25 pada aspek kelayakan isi, 81,94 pada aspek kegrafikan, dan 82,50 pada aspek kebahasaan dengan skor maksimal 100. Hasil penelitian menunjukkan bahwa desain Lembar Kerja Praktikum dengan pendekatan inkuiri terbimbing dikategorikan sangat layak dan dapat meningkatkan keterampilan laboratorium dan pengetahuan siswa.